Generation and maintenance of predation hotspots of a functionally important herbivore in a patchy habitat mosaic. (16th October 2017) - Farina, Simone; Oltra, Aitana; Boada, Jordi; Bartumeus, Frederic; Romero, Javier; Alcoverro, Teresa
Abstract: By modifying how critical ecosystem functions are distributed across the landscape, the spatial configuration and characteristics of patches can play a strong role in structuring communities. In strongly predator‐controlled ecosystems, this patchy distribution of function can have complex downstream consequences, subjecting some areas to disproportionately high rates of predation, leaving other areas susceptible to herbivore outbreaks. In this study, we assess how spatial attributes at patch and landscape scales potentially influence the spatial and temporal distribution of predation on a functionally important herbivore in a patchy Mediterranean marine macrophyte community characterized by strong top‐down control. We experimentally tracked how predation risk of tethered sea urchins varied across space over a 10‐day period in a patchy seagrass meadow. We related these patterns with patch and landscape‐level attributes across the habitat mosaic. At the level of the patch, predation risk was the highest in seagrass patches with low canopies, without access to sheltering rocks. Scaling up to the landscape mosaic however, predation risk increased in dense aggregations of patches with high perimeter‐to‐area ratios close to rocky habitats. Predation aggregated in spatially explicit hotspots and coldspots that were maintained through time. Interestingly, this pattern of predation risk correlated well with the natural abundance of sea urchins. Our results show that spatial patch configuration can be a strong mediator of top trophic functions in marine ecosystems, causing significant clumping in the way predation—and therefore herbivory—are distributed across space. Given the importance of top‐down control for these shallow marine ecosystems, it is crucial to incorporate landscape attributes in understanding the impact of functionally important herbivores on highly fragmented habitats. A plain language summary is available for this article. Abstract : Plain Language Summary